Servant Leadership, Perceived Organizational Support, Job Embeddedness, Job Satisfaction, dan Perceived Supervisor Support terhadap Turnover Intention - Erlian Saputra; Tantri Yanuar R. Syah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
High employee turnover intention can be a big problem for several company. Recruiting replacements for employees who want to resign can be costly. The purpose of this study is to identify the effect of Servant Leadership on Perceived Organizational Support, Job Embeddedness, Job Satisfaction and Turnover Intention, the effect of Perceived Organizational Support, Job Embeddedness, Job Satisfaction on Turnover Intention with the moderating role of Perceived Supervisor Support. This research was conducted using purposive sampling method involving 225 respondents. Data were analyzed using the Structural Equation Model (SEM) with SmartPLS 4. The findings in this study are in the moderating effect of Perceived Supervisor Support strengthening the relationship of Job Embeddedness on Turnover Intention. Meanwhile, the other moderating variables have no effect on Turnover Intention. Managerial implications contained in this study for workers in companies and researchers by applying Servant Leadership in companies, increasing Perceived Organizational Support, increasing Job Embeddedness, increasing Job Satisfaction in order to reduce the level of Turnover Intention.